Targeted drug strategies for cancer and inflammation - Jackman, Ann L.; Christopher P.; SpringerLink (Online service). (Boston, MA Springer US, 2011)
The discoveries highlighted in this book parallel the emergence of innovative -molecular targeted? small molecules and monoclonal antibodies, i.e. agents that target proteins within highly activated signal transduction pathways that control proliferation. Many of the tumor-targeted strategies described within cross the boundaries between what?s considered to be -molecular targeted; versus conventional systemic therapy. However, the main theme of this volume is the folate receptor (FR), with much of the content focused on its basic biology and regulation as well as its exploitation for targeted therapy and diagnostic imaging.
Biological Role, Properties and Therapeutic Applications of the Reduced Folate Carrier (RFC-SLC19A1) and the Proton-Coupled Folate Transporter (PCFT-SLC46A1) -- Folate Receptors and Therapeutic Applications -- Hormonal Control of Folate Receptor Genes -- Folate Receptor Targeted Radionuclide Imaging Agents -- Folate receptor targeted thymidylate synthase inhibitors -- Discovery of novel antifolate inhibitors of de novo purine nucleotide biosynthesis with selectivity for high affinity folate receptors and the proton-coupled folate transporter over the reduced folate carrier for cellular entry -- Folate-receptor targeted cancer chemotherapy -- Anti-FR antibody generation and engineering: development of new therapeutic tools -- Folate Receptor Positive Macrophages: Cellular Targets for Imaging and Therapy of Inflammatory and Autoimmune Diseases -- Targeting Activated Macrophages via a Functional Folate Receptor for Potential Treatment of Autoimmune/Inflammatory Disorders.-.
Electronic reproduction.
Keywords: Cancer--Chemotherapy.; Neoplasms--drug therapy; Antineoplastic Agents; Drug Delivery Systems; Electronic books